A Qualitative Understanding of Motivations, Preferences, and Attitudes Toward Adherence-Based Technology. (17th December 2021) - Zhang, Shenghao; Gray, Nicholas; Dilanchian, Andrew; Carr, Dawn; Lustria, Mia; Boot, Walter; Dieciuc, Michael
Abstract: The future of cognitive assessments and brain-training programs is very likely to involve mobile applications for phones and tablets. However, adherence to these programs over the long haul is notoriously low. In an effort to countervail this trend, we ran online focus groups with both older and younger adults to understand from a user-centered perspective how to better design apps to increase adherence. Using thematic content analysis (Braun & Clarke, 2006) with an inductive bottom-up approach (Frith & Gleeson, 2004), we found a surprising number of common themes across older and younger adults that superseded many of their superficial differences. For instance, both younger and older adults were reluctant to engage in the program unless it had some obvious perceived benefit; both wanted the program personalized to their individual preferences; both wanted the ability to customize features and reminders; and both generally agreed that the tasks had to be fun.